2001
DOI: 10.1074/jbc.m101558200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel Human Galactose 3-O-Sulfotransferase That Transfers Sulfate to Galβ1→3GalNAc Residue in O-Glycans

Abstract: We have identified a novel galactose 3-O-sulfotransferase, termed Gal3ST-4, by analysis of an expression sequence tag using the amino acid sequence of human cerebroside 3-sulfotransferase (Gal3ST-1). The isolated cDNA contains a single open reading frame coding for a protein of 486 amino acids with a type II transmembrane topology. The amino acid sequence of Gal3ST-4 revealed 33%, 39%, and 30% identity to human Gal3ST-1, Gal␤133/ 4GlcNAc:33-sulfotransferase (Gal3ST-2) and Gal␤13 4GlcNAc:33-sulfotransferase (Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 42 publications
(45 reference statements)
1
43
0
1
Order By: Relevance
“…13) Briefly, the labeled oligosaccharides were dissolved in 20 µl of 75 mM sodium metaperiodate, 75 mM sodium acetate (pH 5.3) and incubated at 4°C for 24 h in the dark. After destruction of excess periodate, 300 µl of 0.1 M sodium borate (pH 9.0) containing 0.1 M sodium borohydride was added, and the solution stood for 1 h at room temperature.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…13) Briefly, the labeled oligosaccharides were dissolved in 20 µl of 75 mM sodium metaperiodate, 75 mM sodium acetate (pH 5.3) and incubated at 4°C for 24 h in the dark. After destruction of excess periodate, 300 µl of 0.1 M sodium borate (pH 9.0) containing 0.1 M sodium borohydride was added, and the solution stood for 1 h at room temperature.…”
Section: )mentioning
confidence: 99%
“…13) cDNA cloning of Gal3ST-1 The cDNA encoding for Gal3ST-1 9) was amplified from "Super Script" human testis cDNA library (Life Technologies, Inc., Rockville, MD) by PCR. Oligonucleotide primers used for the PCR were 5′-tttaagcttGTCTGAGATGCTGCCA-3′ (forward primer) and 5′-tttggatccTGGGACGTCACCACCG-3′ (reverse primer).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Gal3ST-4 is the fourth member of the Gal:→3-sulfotransferase family that catalyzes the C-3 sulfation of galactoses in O-linked glycoproteins [5]. It has been shown that sulfation of the glycan chains is associated with the specific physiological functions of the various glycoproteins.…”
Section: Dear Editormentioning
confidence: 99%
“…Thus, it can be conceived that dysfunction of GAL3ST4 by genetic mutations will have a great effect on the sulfation of the various target glycoproteins. The four members of the Gal:→3-sulfotransferase family share 30%-40% amino acid sequence identity, but each of them shows distinct substrate specificities [5]. Although it has been shown that the Gal3ST-4 is highly specific for the core 1 structures generated in the O-linked glycans [10], future studies are needed to unravel the exact downstream targets or pathways of Gal3ST-4 that contribute to the development of familial PE.…”
Section: Dear Editormentioning
confidence: 99%